Strategic fast supply demand-chains in a network context: opportunistic practices that can destroy supply chain systems - Crespo de Carvalho, J.; Martins, A.; Ramos, T.; Dias, E.B. (American Journal of Industrial and Business Management, 2014)
This paper has a conceptual character and explores an approach between transaction cost analysis theory and network theory when applied to supply chains in a broader context: industrial management research. This approach raises the assumptions that fast supply chains, i.e., supply chains made of short time relationships and multiple partners can contribute to destroying trust and collaboration between companies, ending up by stressing actual systems’ arrangements in somehow stable supply chains/network chains. As a consequence, transforming them in distrust arrangements and thus giving birth to new (old) approaches based only on transaction cost analysis theory: opportunism and limited rationality as the continuum for relationships between companies in a globalized world with numerous potential agents/companies that can play several roles. Too high levels of entropy can show this reality: the number of potential players (suppliers, customers or complementors) with theoretically equal probability of establishing partnerships with one focal company in a supply chain or network arrangement is excessive in relation to the number of current suppliers, customers and complementors, and for that reason, the focal company is somehow dissipating energy in identifying several potential players and in a state of giving one way or another equal importance to them all, situation that can affect stable relations with current partners. Theoretically, this will create what looks like strategic fast supply—demand chains or network chains: fast because they are rapidly settle down and fast as they are also rapidly dismantled. Those arrangements are the ones responsible for several possible and fast relations (internalizing resources from the environment and/or externalizing resources to the environment) but, anyway, contributing to loose trust, credibility and running against profitable games with partners already involved with focal companies in stable supply chains.